Employee engagement during COVID-19 in Malaysia - Mustaffa, Amira; Lajuma, Surianti; Wider, Walton (Frontiers in Sociology, 2022)
This objective of this study was to examine the effects of communication, training and development, and transformational leadership on employee engagement during COVID-19 in Malaysia. Four hundred individuals were recruited, and data were analyzed using partial least square structural equation modeling (PLS-SEM). Communication, training and development, and transformational leadership were found to positively affect employee engagement. In the midst of the COVID-19 outbreak, this study investigated the aforementioned factors as part of the reciprocal process between the employee and the employer and their effects on employee engagement, thereby making original theoretical contributions. This study also provides vital insights for businesses to consider when designing effective employee engagement plans for future well-being in the workplace.